The action of the testa upon the germination of seeds of Cucumis anguria L. - Cardoso, V. J M [UNESP]; Felippe, G. M. (Institute of Experimental Botany, 1988)
In negatively photoblastic seeds of Cucumis anguria L. the scarification of micropyle overcame the inhibitory effect of white light , although far-red radiation inhibited the germination in both intact and scarified seeds. The moistened testa powder transmitted more far-red than red radiation. Thus the testa could act as a filter of radiation and maintain a high far-red/red ratio at the photosensitive site of the embryo, which must be localized near the micropyle. © 1988 Academia.